NPM1 as a potential therapeutic target for atypical teratoid/rhabdoid tumors - Ji Hoon Phi; Choong-Hyun Sun; Se-Hoon Lee; Seungmook Lee; Inho Park; Seung Ah Choi; Sung-Hye Park; Ji Yeoun Lee; Kyu-Chang Wang; Seung-Ki Kim; Hongseok Yun; Chul-Kee Park (BMC Cancer, 2019)
Abstract Background Atypical teratoid/rhabdoid tumors (AT/RTs) are highly malignant brain tumors with inactivation of the SMARCB1 gene, which play a critical role in genomic transcriptional control. In this study, we analyzed the genomic and transcriptomic profiles of human AT/RTs to discover new druggable targets. Methods Multiplanar sequencing analyses, including whole exome sequencing (WES), single nucleotide polymorphism (SNP) arrays, array comparative genomic hybridization (aCGH), and whole transcriptome sequencing (RNA-Seq), were performed on 4 AT/RT tissues. Validation of a druggable target was conducted using AT/RT cell lines. Results WES revealed that the AT/RT genome is extremely stable except for the inactivation of SMARCB1. However, we identified 897 significantly upregulated genes and 523 significantly downregulated genes identified using RNA-Seq, indicating that the transcriptional profiles of the AT/RT tissues changed substantially. Gene set enrichment assays revealed genes related to the canonical pathways of cancers, and nucleophosmin (NPM1) was the most significantly upregulated gene in the AT/RT samples. An NPM1 inhibitor (NSC348884) effectively suppressed the viability of 7 AT/RT cell lines. Network analyses showed that genes associated with NPM1 are mainly involved in cell cycle regulation. Upon treatment with an NPM1 inhibitor, cell cycle arrest at G1 phase was observed in AT/RT cells. Conclusions We propose that NPM1 is a novel therapeutic target for AT/RTs.